Experimental Comparison and Validation in the Simulation of Natural and Forced Convection Used in Photovoltaic Setup - Sagar V Wankhede, Jitendra A Hole, R. Shenbagalakshmi, Bhushan L Patil (International Journal of Advanced Science and Technology, 2020)
The majority of the research scholars are constantly endeavoring to enhance the efficiency of solar photovoltaic (PV) setup which consists of sunlight based cells. To control PV setup efficiency, it should be kept under the most permissible temperature. In like manner, the extra in heat should be scattered accurately so as to evade unnecessarily high temperatures, which negatively affect the electrical behavior of the cell. Accordingly, an experimental investigation is introduced to increase performance of a PV setup using natural and forced convection cooling techniques. The outcomes show that the use of forced convection cooling technique has improved the module efficiency by 1.06%, and power output by means of 2.98 Watt. Keywords: Solar PV Cooling, Natural Convection, Forced Convection, Simulation, Efficiency, Power